The Politics of Fieldwork : Research in an American Concentration Camp - Hirabayashi, Lane Ryo (Book collections on Project MUSE., 1999)
Lane Hirabayashi examines the case of the late Dr. Tamie Tsuchiyama. Drawing from personal letters, ethnographic fieldnotes, reports, interviews, and other archival sources, The Politics of Fieldwork describes Tsuchiyama's experiences as a researcher at Poston, Arizona - a.k.a. The Colorado River Relocation Center. The book relates the daily life, fieldwork methodology, and politics of the residents and researchers at the Poston camp, as well as providing insight into the pressures that led to Tsuchiyama's ultimate resignation, in protest, from the JERS project in 1944. A multidisciplinary synthesis of anthropological, historical, and ethnic studies perspectives, The Politics of Fieldwork is rich with lessons about the ethics and politics of ethnographic fieldwork.